2013
DOI: 10.2298/sos1302233v
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the mechanical properties of spark plasma sintered hap bioceramics by decreasing the grain size and by adding multi-walled carbon nanotubes

Abstract: Composites based on HAP and oxidized multi-walled carbon nanotubes (o-MWCNT) and monophase HAP materials were processed by spark plasma sintering. Starting from stoichiometric nano-sized HAP powder, monophase bioceramics were obtained with a density close to the theoretical one and with an average grain size of several hundred nanometers to micron dimensions. It was shown that decreasing the sintering temperature resulted in a decrease of the grain size, which affected an increase in the fracture toughne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Therefore, the hardness of the material strongly depends on its density and the effect of grain growth will be small. This is more meaningful, specifically with a process such as spark plasma sintering where the heating rate is high, the sintering temperature is low, and the sintering time is short compared to other conventional sintering processes [22,[49][50][51]. The hardness reported in this study for the Al2124 alloy was higher than the hardness of other alloys, processed under similar conditions, such as Al6061 [27], Al-7Si-0.3Mg [52], and Al-12Si-0.3Mg [31].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the hardness of the material strongly depends on its density and the effect of grain growth will be small. This is more meaningful, specifically with a process such as spark plasma sintering where the heating rate is high, the sintering temperature is low, and the sintering time is short compared to other conventional sintering processes [22,[49][50][51]. The hardness reported in this study for the Al2124 alloy was higher than the hardness of other alloys, processed under similar conditions, such as Al6061 [27], Al-7Si-0.3Mg [52], and Al-12Si-0.3Mg [31].…”
Section: Resultsmentioning
confidence: 99%
“…where t is the crystallite size (nm) and d-is the theoretical density of HAp (3.16 g/cm 3 ).The results suggested that in case of (HAp/PVA) blend the apparent average crystal size is the same by increasing the percentage of the PVA before and after burning.as shown in fig.7a-7bIn case of the presence of MWCNTs the outcomes indicated that the apparent average crystal size increased by increasing the share of the MWCNT beforeburning.as shown in fig.9aBut the opposite occurred after burning as shown in fig 9b where the crystallite size of the HAp/.0003 MWCNT are significantly smaller, with average grain size of 85±29 nm (tab.2). This decrease of the crystallite size can be linked to the presence of carbon nanotubes on the grain boundaries during grain growth [27]. The FTIR analysis showed in Figure (10a) HAp/10%PVA/MWCNTs (0.0005, 0.001, 0.002, and 0.003) gm powders before burning.…”
Section: Sem Analysis Of Porous Hapmentioning
confidence: 97%
“…So the strategy to overcome this weakness is to introduce materials possess good mechanical properties to enhance mechanical properties with HAP as matrix without impairing its bioactivity. Carbon nanotubes have a lot of interest in most of the areas of nanoscience and nanotechnology because of their high chemical and thermal stability, mechanical resistance, flexibility, electrical and thermal conductivity [27][28][29]. Inclusion of small amounts of CNTs in a ceramic matrix should that producing composites with high rigidity and mechanical properties improved compared to single phase ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used method of powder consolidation is conventional sintering method. Densification of hydroxyapatite compacts normally require sintering at 1000 °C or higher temperatures [16,17]. However, low temperatures (400-500 °C) are used to preserve the morphology of initial particles and develop microstructures made by nanosized grains.…”
Section: Introductionmentioning
confidence: 99%